ОРГАНИЗАЦИЯ САМОСТОЯТЕЛЬНОЙ РАБОТЫ СТУДЕНТОВ В УСЛОВИЯХ КРЕДИТНО-МОДУЛЬНОГО ОБУЧЕНИЯ - Пардаева, Х.О. (SCIENCE and SOCIETY, 2022)
The article deals with the organization of independent work of students in the conditions of credit-modular education. Today, the training of future biologists for continuous education and self-education, the formation of the need for them to independently acquire and replenish their knowledge, skillfully and quickly navigate the flow of various information: technical, reference, scientific, is relevant. This can be achieved through the independent work of students, which is discussed in the article.